Texture analysis of sawdust for animal feed - Mohammad Hasif Hafizi Mohd Shukri (2022)
Sawdust is one of the highly potential agricultural wastes that can be used as the animal feed for cattle. This research mainly focuses on the texture of the sawdust that can be affected by the different on container size, the moisture inside the container, the temperature that the sample was stored and the presence of oxygen during fermentation process. The hardness of sawdust can be measured by using the Texture analyzer after the sawdust undergoing fermentation by using yeast as main component for fermentation of sawdust. The duration of fermentation of sawdust are 14 days, During the fermentation process, the hardness of every sample was recorded and stored based on their conditions(different on container size, temperature, moisture and presence of oxygen) was selected during the fermentation process.